Caring experiences and support needs among family caregivers of patients with End Stage Renal Disease (ESRD) in Rwanda: A descriptive qualitative study - Michel Nkuranyabahizi; Lakshmi Rajeswaran; Flavien Ngendahayo; Larissa Umuhire; Jean Claude Shyaka; Violette Dushimiyimana; Geldine Chironda (Elsevier, 2021)
Background: End Stage Renal Diseases (ESRD) is a major public health problem affecting patient and family members directly and indirectly. Little is known about caring experiences and support needs of family caregivers of patients with ESRD. Aim of the study: The aim of this study was to explore the experiences of caring and support needs of the family caregivers of patients with ESRD at selected haemodialysis units in Rwanda. Methodology: This study used a qualitative descriptive design. Purposive sampling was used to select twelve (12) participants. Data were collected using the adopted semi structured interview guide. Data were organized and coded with content analysis being used to create the categories and themes. Results: The emerging themes for caring experiences were: "personal issues", "spiritual issues" and "sense of satisfaction". The need for dialysis policy change, shelter and psychological counselling were highlighted by the family caregivers. Conclusion: The role of the family caregiver in caring for patients with ESRD exposes them to different experiences. Nurses should use the findings to provide support for family caregivers of patients with ESRD.